Efektivitas Layanan Bimbingan Klasikal Dengan Metode Sosiodrama Untuk Menurunkan Perilaku Intoleransi Pada Peserta Didik - Nilawati, Fadhila Aris; I Wayan Dharmayana; Arsyadani Mishbahuddin (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2025)
This study aimed to prove the effectiveness of classical guidance services using the sociodrama method in reducing intolerant behavior among students. The research was conducted using an experimental method with a two-group pre-test post-test control design. The population of this study consisted of tenth-grade students at SMK Negeri 4 Kota Bengkulu, totaling 76 students. The research sample comprised 43 students, including 26 students in the experimental class and 17 students in the control class, who were selected using a purposive sampling technique. Data were collected using an intolerance behavior questionnaire based on a Likert scale. The pre-test and post-test results of the experimental class showed a decrease in the average score from 169 to 103, with a gain score of 66, while the control class decreased from 129 to 122, with a gain score of 7. Hypothesis testing using a t-test yielded a t value of 21.629 with Sig. (2-tailed) = 0.000 (p < 0.05), indicating a significant difference in intolerant behavior between students who received classical guidance services with the sociodrama method and those who received classical guidance without the method. Therefore, the findings showed that classical guidance services with the sociodrama method were effective in reducing intolerant behavior. Keywords: classical guidance, intolerance, sociodrama method